2014
DOI: 10.1186/2251-6581-13-34
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low dose ω-3 poly unsaturated fatty acids on cognitive status among older people: a double-blind randomized placebo-controlled study

Abstract: BackgroundCognitive impairment is a prevalent health problem in older people and its global prevalence tends to increase parallel to the extended life expectancy in world. The beneficial effect of ω-3 PUFAs on cognitive impairment has been demonstrated in some experimental and cohort studies. In this study we aimed to assess the effect of low dose docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) supplementation on cognitive status in the elderly.MethodsIn a double-blind, randomized placebo-controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Daily supplementation of omega-3 fatty acids for 6 months in the OmegAD trial improved cognitive performance in individuals with mild AD (although effects in cognitively normal individuals were less apparent) (Eriksdotter et al, 2015). Indeed, similar results are found in other studies in which dietary supplementation of omega-3 fatty acids improved cognition with the greatest effects observed in those with mild cognitive impairment or at the low end of cognitively normal (Kotani et al, 2006;Lee et al, 2013;Mahmoudi et al, 2014;Hamel et al, 2015;Andrieu et al, 2017;Soininen et al, 2017;Zhang et al, 2018). Moreover, improvements following DHA supplementation may be maintained for a period beyond the DHA treatment (Quinn et al, 2010;Yurko-Mauro et al, 2010;Zhang et al, 2016).…”
Section: Macronutrient: Fatssupporting
confidence: 72%
“…Daily supplementation of omega-3 fatty acids for 6 months in the OmegAD trial improved cognitive performance in individuals with mild AD (although effects in cognitively normal individuals were less apparent) (Eriksdotter et al, 2015). Indeed, similar results are found in other studies in which dietary supplementation of omega-3 fatty acids improved cognition with the greatest effects observed in those with mild cognitive impairment or at the low end of cognitively normal (Kotani et al, 2006;Lee et al, 2013;Mahmoudi et al, 2014;Hamel et al, 2015;Andrieu et al, 2017;Soininen et al, 2017;Zhang et al, 2018). Moreover, improvements following DHA supplementation may be maintained for a period beyond the DHA treatment (Quinn et al, 2010;Yurko-Mauro et al, 2010;Zhang et al, 2016).…”
Section: Macronutrient: Fatssupporting
confidence: 72%
“…For example, most studies used fish oil as a supplementation, providing both DHA and eicosapentaenoic acid (EPA), with the latter also potentially contributing to the preventive effect of fish oil against cognitive decline. Moreover, the protective role of DHA against age-related cognitive decline may depend on APOE genotype [84] and on the degree of cognitive decline at baseline, and may be stronger in those with the mildest cognitive impairment [85][86][88][89][90][91]. This suggests that DHA may be more efficient as a preventive intervention rather than as a curative treatment.…”
Section: Randomized Clinical Trialsmentioning
confidence: 88%
“…Kotani et al [145] demonstrated that DHA (240 mg/day) supplementation significantly ameliorated scores of immediate memory and attention in adults with MCI, but not in the AD patients who were provided with the same dose of supplementation for the same period. One study reported no significant prevention of cognitive decline in older people with MCI given DHA over six months [146]. Lopez et al [147], in their dietary intervention study, reported that fish intake was associated with lower odds of developing AD, but this did not reach statistical significance.…”
Section: Epidemiological Studiesmentioning
confidence: 97%